Reports on the Processing of Exotic Fruits - Richter Reis, Felipe; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents exotic fruit processing as a way to obtaining traditional and innovative fruit products by means of various food processing technologies. Built on the basis of specific, up-to-date and reliable scientific reports, it is a unique document for instructing researchers, processors and enthusiasts in the field of exotic fruit processing.
Introduction -- Exotic fruits: agricultural, botanical and commercial aspects -- Selected reports on the chemical characterization of exotic fruits -- Traditional Exotic Fruit-Based Products -- Innovative Exotic Fruit-Based Products.
Keywords: Food science; Chemistry, Technical; Food Science; Industrial Chemistry